Efficacy and Safety of Radio Frequency Ablation for Benign Thyroid Nodules: Initial Clinical Experience in United Arab Emirates - Kwang Hwi Lee; Eui Yong Jeon; Sung June Jang (The Arab Journal of Interventional Radiology, 2022)
Objectives Radio frequency ablation (RFA) to treat thyroid nodules is well known as one of alternative therapeutic modalities. This study aimed to investigate the efficacy and complications of RFA to treat symptomatic benign thyroid nodules in United Arab Emirates. Materials and Methods Eight-nine benign thyroid nodules of 63 patients were enrolled, who were treated by percutaneous ultrasound (US)-guided RFA from 2017 to 2020, and had following US examinations during 12 months after RFA procedure. Symptomatic score with 10-cm visual scale, cosmetic score with four-point scale, and US findings (nodule diameter, volume, composition and vascularity) were compared before and after RFA procedures. RFA-related complications (hematoma, voice change, hypothyroidism, and hyperthyroidism) were assessed. Statistical Analysis Paired t test was applied to compare laboratory findings before and after RFA procedure. Multiple linear regression analysis was applied to determine significant factors to predict the efficacy of RFA. One-way analysis of variance was applied to compare volume reduction rate (VRR) at 3, 6, and 12 months. Results Symptomatic and cosmetic scores were significantly improved (pre-RFA vs. post-RFA; 6.07 ± 1.89 vs. 2.06 ± 1.09, 2.94 ± 0.84 vs. 1.27 ± 0.51, p< 0.001). Nodule diameter (cm), volume (mL) at pre-RFA, post-RFA 3 months, 6 months, and 12 months were 3.86 ± 1.26, 2.64 ± 1.14, 2.06 ± 1.09, 1.82 ± 1.14, and 18.8 ± 18.79, 8.82 ± 12.42, 4.47 ± 5.59, 4.11 ± 9.17 (p< 0.001). VRR (%) was 52.81 ± 23.48 at post-RFA 3 months, 79.77 ± 16.91 at 6 months, and 82.08 ± 19.54 at 12 months. Composition of solidity was a significant predictive factor, related to VRR at post-RFA 12 months (p = 0.003). Complication rate was 12.7% (8 of 63 patients). Major complications did not occur. Conclusion RFA can be an effective and safe alternative modality to treat benign thyroid nodules, and be preferable to treat symptomatic cystic thyroid nodules in Middle East population.